Transforming Classroom Practice Through Effective Teaching Methods: Evidence from Educational Research - Abid Rahman Asrowi, Tiara Agustina (Lembaga Bale Literasi, 2025)
This study investigates how effective teaching methods transform classroom practices by integrating evidence from both quantitative and qualitative data. Employing a mixed-methods research design, the study involved 120 students and 10 English as a Foreign Language (EFL) teachers selected through cluster random and purposive sampling techniques. Data were collected using questionnaires, classroom observations, semi-structured interviews, and document analysis to provide a comprehensive understanding of instructional practices and learning outcomes. The quantitative findings revealed that students demonstrated highly positive perceptions of the implemented teaching methods, with an overall mean score of 4.14 (83%), categorized as very good. Among the measured variables, contextual learning (86%) and collaborative engagement (84%) showed the highest levels of effectiveness, followed by student-centered learning (82%) and learner autonomy (79%). Inferential statistical analysis further indicated significant differences (p < 0.05) in learning outcomes between students taught using innovative approaches such as Problem-Based Learning (PBL) and Project-Based Learning (PjBL) and those taught using conventional methods, with PjBL showing the strongest impact. Qualitative findings supported these results, revealing increased student engagement, improved collaboration, and more meaningful learning experiences. Students were observed to be more active, confident, and motivated when participating in interactive and context-based learning activities. However, several challenges were identified, including time constraints, diverse student abilities, and the need for greater teacher readiness in implementing innovative pedagogies. Therefore, the study concludes that effective teaching methods significantly enhance classroom practices by promoting active learning, collaboration, and improved academic performance. These findings suggest that adopting student-centered approaches is essential for creating dynamic and meaningful learning environments, while also highlighting the importance of addressing implementation challenges to ensure sustainable educational transformation.